Assessment of the bypass of obturation materials beyond fractured instruments after using different obturation techniques in simulated curved canals (An in-vitro study). - Ammar Aziz Lateef; Mohammed Rasheed Hameed; Noor Hayder Fadhil; Ahmed Hamid Ali (PLoS ONE)
This study evaluated the extent to which obturation materials bypass fractured endodontic instruments positioned in the middle and apical thirds of severely curved simulated root canals using different obturation techniques. Sixty resin blocks with simulated root canals were used, each with a 50° curvature, a 6.5 mm radius of curvature, and a length of 16.5 mm, prepared to an ISO #15 diameter and taper. Canals were shaped using ProTaper Universal files (Dentsply Maillefer) attached to an X-smart Plus endo motor (Dentsply), set at 3.5 Ncm torque and 250 rpm, up to size S2 at working length. To simulate fractures, F2 and F3 files were weakened 3 mm from the tip, then twisted to break in the apical and middle sections of the canal, respectively. All samples were sealed with GuttaFlow 2 and divided into three groups (n = 20/group) according to obturation technique: A) single cone, B) lateral condensation with a rotary spreader, and C) softcore obturators. Each group was then divided into two subgroups (n = 10) based on the instrument fracture location (1 = apical, 2 = middle). The linear intrusion of obturation materials through the fractured instruments was measured using ImageJ software and analyzed statistically with ANOVA, Tukey tests, and independent t-tests, with significance set at p<0.05. Material bypass in group B1 (3.27 ± 0.63 mm) was significantly greater than in group A1 (2.39 ± 0.44 mm) and group C1 (2.91 ± 0.77 mm). In group C2, bypass (5.76 ± 0.64 mm) was significantly higher than in group A2 (3.82 ± 0.2 mm) and group B2 (2.27 ± 0.96 mm). Additionally, bypass in group A2 was greater than in group B2, and group B1 had more bypass than B2, while group C2 exceeded C1. The lateral condensation technique with a rotary spreader and softcore obturators increased the bypass of obturation materials through fractured instruments in simulated curved canals. These techniques may thus enhance material flow in endodontic procedures involving instrument fractures.